Part-time work and sickness absence - an organization-level analysis - Dag Ingvar Jacobsen; Viktoria Fjelde (BMC, 2023)
Abstract Background Absenteeism is consistently higher in public than in private organizations, as is the use of part-time employment. The aim of this study is to identify whether there is a relationship between part-time work and sickness absence at the organizational level. Methods The data is a six-year panel for the full population of Norwegian municipalities (N = 422), linking objective register data on both part-time employment and sickness absence. Using OLS regression with fixed effects for municipality and time, we estimate the statistical effects of the municipalities' use of part-time work on sickness absence. Results The bivariate correlation between percentage position at the municipal level and percentage sickness absence is positive and significant (Pearson's r = .25, sig LE 0.01). When controlling for fixed effects for municipality and time, as well as municipality economy, municipality size, ratio of female employees in the municipality and characteristics of the general population, the multivariate regression coefficient is still positive but insignificant (coefficient = 1.56, robust standard error = 1.31). Conclusions The main findings are that the organizations' use of part-time work is unrelated to sickness absence indicating that organizations with extensive use of part-time work do not experience higher levels of absenteeism than those having less extensive use of part-time employees.